Effect of temperature on gonadal differentiation and growth of Leporinus friderici - de Souza, Thiago Gonçalves [UNESP]; de Abreu, Mariana Roza [UNESP]; Kuradomi, Rafael Yutaka [UNESP]; Batlouni, Sergio Ricardo [UNESP] (FapUNIFESP (SciELO), 2024)
This study aimed to investigate the effect of temperature on gonadal differentiation, growth, survival, and sex ratio of Leporinus friderici reared at 25 °C or 29 °C from 50 to 240 days after eclosion (DAE) in a water recirculation system. A total of 110 fish at 50 DAE (6.7 ± 0.1 cm and 6.1 ± 0.3 g) were equally and randomly distributed in 10 boxes (90 L) (11 fish/box, 5 boxes/temperature). One fish from each experimental unit was randomly sampled at 50, 70, 90, 110, 130, 150, 170, 190, 210 and 240 DAE. Female gonadal differentiation started at 150 DAE (11.4 ± 0.0 cm and 16.4 ± 0.0 g) at 25 °C and at 170 DAE (10.7 ± 0.7 cm and 27.7 ± 8.5 g) at 29 ºC, while testes differentiation only occurred at 29 °C from 190 DAE (12.1 ± 0.0 cm and 38.0 ± 0.0 g). Of 50 fishes sampled in each condition, 17 (12 females and five males) and three (three females) displayed gonadal differentiation at 29 °C and 25 °C, respectively. Final biometric values at 29 °C were twice those obtained at 25 °C, reaching 13.9 ± 0.65 cm and 57.3 ± 10.12 g versus 11.2 ± 0.39 cm and 28.5 ± 2.95 g, respectively. While temperature clearly influenced gonadal differentiation and growth, it had inconclusive effects on sex ratio. The higher temperature (29 °C) has direct implications for the production of this species, as it accelerates growth without causing mortality.
Keywords: females; fish; gonads; sex determination; wild